A novel digital control scheme for power management in a hybrid energy-source environment pertaining to electric vehicle applications - Mathesh, G.; Saravanakumar, R. (Frontiers in Energy Research, 2023)
In electric vehicle, the utilization of various input power sources demand an appropriate integration. This integration inevitably questions the effectiveness of a suitable power management system. The integration of sources causes complexity in power conversion and programming errors while switching between the sources and brings difficulties in real-time implementation. This study presents a novel digital control scheme specific to the integration of solar, battery, and fuel cell to solve these issues and also explains the power management system in different controllers for electric vehicles. The proposed scheme checks the reference currents based on the power generated by the different sources needed to meet the instantaneous demand from the permanent magnet synchronous machine, which is widely used in electric vehicles. The methodology constitutes maximum power point tracking in solar panels at every second of the day, retaining constant voltage in the DC bus and managing the power flow from sources to the permanent magnet synchronous machine based on the power availability from different sources. The power flow to a control module dedicated to permanent magnet synchronous machine control is considered. The major contribution of the paper is the design and development of a power management system for an electric vehicle with a novel digital control scheme. Power management is achieved with the aid of a digital controller using real-time solar data for a periodically fluctuating load demand in MATLAB/Simulink and also in an experimental investigation, the results of which are discussed.